2009
DOI: 10.1016/j.mib.2009.09.010
|View full text |Cite
|
Sign up to set email alerts
|

White–opaque switching in Candida albicans

Abstract: SummaryThe human commensal yeast Candida albicans undergoes an epigenetic switch between two distinct types of cells, referred to as white and opaque. These two cell types differ in many respects, including their cell and colony morphologies, their metabolic states, their mating behaviors, their preferred niches in the host, and their interactions with the host immune system. Each of the two cell types is heritable for many generations and switching between them appears stochastic; however, environmental cues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(122 citation statements)
references
References 40 publications
1
119
0
2
Order By: Relevance
“…Production of Msb2 could subsequently provide the same protection to E. faecalis, leading to long-term colonisation of the root canal. It has also been shown that dual-species biofilms of these two organisms upregulate expression of the C. albicans transcriptional regulator WOR1, to which controls the phenotypic switch from the white to opaque cell type, that has been shown to be less susceptible to the innate immune system [113,114]. C. albicans has also demonstrated the ability to promote the growth of E. faecalis in the gastrointestinal tract [115,116].…”
Section: Endodontic Infections: Sinister Encounters In the Darkmentioning
confidence: 99%
“…Production of Msb2 could subsequently provide the same protection to E. faecalis, leading to long-term colonisation of the root canal. It has also been shown that dual-species biofilms of these two organisms upregulate expression of the C. albicans transcriptional regulator WOR1, to which controls the phenotypic switch from the white to opaque cell type, that has been shown to be less susceptible to the innate immune system [113,114]. C. albicans has also demonstrated the ability to promote the growth of E. faecalis in the gastrointestinal tract [115,116].…”
Section: Endodontic Infections: Sinister Encounters In the Darkmentioning
confidence: 99%
“…It has been reported that 3 Candida species (C. albicans, C.dubliniensis, and C. tropicalis) can undergo white-opaque switching, which is linked to the ability to cause systemic and cutaneous infections and to undergo sexual mating. 13,[19][20][21]25,34,35 We have recently discovered that C. albicans can also exist as a novel cell type, the gray phenotype, 25 which is distinct from the well-studied white and opaque cell types. 21 In the current study, we report the discovery of the gray phenotype and white-gray-opaque transitions in C. dubliniensis.…”
Section: Discussionmentioning
confidence: 99%
“…White-opaque switching in C. albicans has been intensively investigated in the previous decade. [18][19][20][21] White and opaque cells are 2 distinct and heritable cell types that differ in cellular morphologies, global gene expression profiles, susceptibility to host immune cells, and mating competency. White cells are round and relatively small, while opaque cells are elongated and large.…”
Section: Introductionmentioning
confidence: 99%
“…C. albicans cells can alternate between white and opaque forms, and these two heritable states show marked differences in mating, immune cell interactions and virulence [70,71]. The master transcription factor regulating the white-opaque transition is Wor1, which ensures stable switching to the opaque state by positive feedback on its own promoter [72][73][74].…”
Section: Investigation Of Chromatin Structure and Transcriptional Regmentioning
confidence: 99%